Citizen Science and Wildlife Conservation: Lessons from 34 Years of the Maine Loon Count - Stockwell, Sally; Gallo, Susan (Maine Policy Review, 2017)
Since the early 1980s—long before the term citizen science was widely adopted— Maine Audubon has engaged thousands of dedicated volunteers in myriad wildlife surveys and studies, from bat colony monitoring to spring amphibian surveys to loon counts. In this article, the authors describe some of those citizen science projects and use the longest-running program, the Maine Loon Project and its annual Loon Count, to showcase what it takes to run a successful program. They also review key lessons learned from these projects over the last three decades.
Keywords: Maine; citizen science; Maine Audubon Loon Count; wildlife monitoring